Peran Penggunaan Website dan Kualitas Produk dalam Keputusan Pembelian pada Produk Fashion - Adri Arisena Arisena; Gijanto Purbo Suseno; Mohammad Fahreza (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
Consumer decision making is an integration process that combines knowledge to evaluate two or more alternative behaviors and choose one of them. The result of this integration process becomes a choice that is presented cognitively as a desire to behave. This research is motivated by the problem of declining sales over the last two years. This decrease in sales is allegedly due to the unattractive appearance of the website in accordance with 7C, namely context, content, community, customization, communication, commerce and connection, then changes in consumer perceptions of product quality resulting in a decrease in purchasing decisions. There are three variables in this research, namely the use of the website ( X1), product quality as the independent variable (X2) and purchase decision as the dependent variable (Y), with data sources from the literature obtained from the results of literature studies and from references in the form of book and internet sources related to research. The results of this study indicate that the use of the website and product quality are considered quite good by consumers and consumers feel confident about their purchasing decisions.